Oxidomolybdenum(IV), -(V), -(VI) complexes with elevance to molybdenum enzymes: oxygen atom transfer, redox chemistry and EPR spectroscopy - Heinze, Katja; Fischer, Andreas (European journal of inorganic chemistry, 2010)
The cis-dioxidomolybdenum(VI) complex Mo(NN′)2O2 (1) [(NN′) = N-(4-hydroxyphenyl)-2-pyrrolatocarbaldimine] transfers one oxygen atom to phosphanes PMenPh3-n (n = 0-3) to give quantitatively the respective phosphane oxides OPMenPh3-n (OAT, oxygen atom transfer). The kinetics of these OAT reactions has been investigated spectrophotometrically. When offering excess PMenPh3-n (n = 1-3), oxido(phoshane)molybdenum(IV) complexes Mo(NN′)2O(PMenPh3-n) 5a-5c are isolated and characterized by multinuclear NMR spectroscopy (1H, 13C, 31P, 15N), IR spectroscopy, UV/Vis spectroscopy and mass spectrometry. The redox chemistry of the molybdenum(IV) complexes 5a-5c and of molybdenum(VI) complex 1 has been probed by preparative one-electron oxidation and reduction, respectively, in combination with EPR spectroscopy under strictly anhydrous conditions. The reactivity of the resulting MoV species (ligand substitution, protonation, silyation) has been investigated to shed further light onto the biomimetic catalytic cycle of OAT from water to substrates in combination with two coupled electron proton transfer reactions (CEPT).